Barcoding for diatoms in the Yangtze River from the morphological observation and 18S rDNA polymorphic analysis. (April 2019) - Li, Zheng; Liu, Xiaorong; Yu, Yanfang; Huang, Huijie; Li, Xingling; Ji, Qiang; Li, Kai; Yu, Youjia; Li, Ding; Mao, Zhengsheng; Pu, Yan; Chen, Peng; et al.
Abstract: In forensic science, the determination of diatoms bears several goals, for example to estimate the post mortem interval (PMI), to determine the cause of death of a corpse found in water as well as to further locate the suspected drowning site. However, to identify diatoms using morphological method beyond the genus level is difficult and requires expert knowledge. During the last decade, a new concept of DNA barcode is becoming a promising approach to identify the taxa of diatoms. In the present study, we performed a diatom morphological analysis covering 10 different water areas in Nanjing section of the Yangtze River. The diatoms were classified to the 'genus' level by using optical microscope and electron microscope. According to the morphological study results, we further designed and analyzed the 18S rDNA sequences as barcodes at the 'species' level. Our study established the morphological and DNA barcoding profile for the diatoms in Nanjing section of the Yangtze River for the first time which will be of great significance for the using of diatoms in forensic application. The results indicated that detailed analysis of selected diatom DNA barcodes can be used as a useful tool for forensic applications.